PENGARUH FINANCIAL PERFORMANCE TERHADAP STOCK PRICE DI ERA PANDEMI COVID-19 PERUSAHAAN FARMASI DI INDONESIA - Eva Wany; Vira Martyasari; Ismangil Ismangil; Budi Prayitno (Media Mahardhika, 2022)
This study examines and analyzes the effect of financial performance using the ratio p Return on Equity Current Ratio, Debt to Equity Ratio, market value ratio Earning Per Share and sales growth to stock prices in the COVID-19 era. The population taken is pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the first quarter of 2020. The sample method used is the purposive sampling method where there are 10 companies that are the samples of this study. The statistical analysis method used in this study is multiple linear regression with SPSS 23.0,. The results obtained from the F test show that the financial performance variables ROE, CR, DER, EPS and sales growth have a significant effect on stock prices in the COVID-19 era. in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). The results obtained from the t test show that partially ROE, EPS and sales growth have a significant effect on stock prices, while CR and DER have no significant effect on stock prices in the COVID-19 era in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX).